DESIGN AND SAFETY FACTOR SIMULATION OF AN AUTOMATED FEEDER FOR BLANKING MACHINES - Wijayanto, Hendi Lilih; Zulfianti; Yusdianto; S, Hairun Apriadi Ramadhan; Usman; Usman (Universitas Muhammadiyah Surakarta, 2025)
The displacement of the stainless-steel plate to the printing work area is still managed manually by theoperator. Additionally, there is no clear benchmark to determine whether the plate is in the correct position andaligned according to the printed pattern. Thus, the print results are frequently less than perfect and require a longprocess. To address these conditions, an additional feeder is required with an automatic system that can operatein conjunction with the blanking machine, simplifying the operator's work and enhancing the blanking processefficiency. The objectives of this research are to determine the design of the feeder machine design by the needsand specifications of the machine, to discover the value of the safety factor of the Feeder machine design, and toreveal the movement system of the Feeder machine design using SolidWork 2019. This final project was carriedout in June 2023 at Politeknik Industri Logam Morowali (PILM) in Labota Village, Bahodopi District, MorowaliRegency, Central Sulawesi Province. The results show that: Researchers can make a design with the provisionsof a length of 550 mm and a width of 250 mm, while the known safety factor value for both areas is declared safesince it has Factor of Safety (FOS) value of 1 and the design movement system displayed on the animation systemin SolidWork 2019 software.